Currículos de formação de professores de educação física no estado do Pará: conteúdos curriculares, concepções pedagógicas e modelos de profissionalidade - ARANHA, Otávio Luiz Pinheiro (Universidade Federal do Pará, 2012)
The study is part of the Graduate Program in Education at the Federal University of Pará, in the line of "Curriculum and Teacher Training" as part of the productions of the research group "Includere." Its object of study the curriculum adopted by the proposed training courses for teachers of Physical Education of the State of Pará, from 2000 to 2010. It has the following problem: what conceptions of physical education teachers and models of professionalism guide the curriculum adopted by the prescribed graduate courses in Physical Education of the State of Para? It is based methodologically on the historical and dialectical materialism, in the qualitative study and documentary. Performs content analysis (Trivino, 1987, France, 2008) of the Political Pedagogical Project (PPP) of six graduate courses in Physical Education of the State of Pará Discusses theoretical and conceptual questions about curriculum, selection of curricula, pedagogical concepts of Physical Education, profession, proletarianization and teacher professionalism throughout the sections. Notes that the National Curriculum Guidelines for Undergraduate Courses in Physical Education (DCNEF) adopt the pedagogical concept of physical fitness model of professionalism and technical and rationalizing. In the six curricula studied Physical Education, notes that the predominant pedagogical conceptions are renewed health and Phenomenology in the presence of Developmental, Competitive and Criticalovercome, however, if they have hybridized in the curriculum. Identifies the model adopted in the teaching profession courses investigated was the technical and rationalizing, despite the progressive use of terminology and contradictions between the texts and curriculum structure of the PPP. Investigation concluded that curricula reproduce the overall eterminations of capital formation in the project, but it is possible to resist the official norms, as evidenced by the curriculum of Physical Education Course at the University of Pará, although this presents with limitations on the formative project desired.